2017
DOI: 10.1038/nmeth.4511
|View full text |Cite
|
Sign up to set email alerts
|

A permanent window for the murine lung enables high-resolution imaging of cancer metastasis

Abstract: Stable, high-resolution intravital imaging of the lung has become possible through the utilization of vacuum-stabilized imaging windows. However, this technique is extremely invasive and limited to only hours in duration. Here we describe a minimally invasive, permanently implantable window for high-resolution intravital imaging of the murine lung that allows the mouse to survive surgery, recover from anesthesia, and breathe independently. Compared to vacuum-stabilized windows, this window produces the same hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
174
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 145 publications
(180 citation statements)
references
References 33 publications
6
174
0
Order By: Relevance
“…For example, the chronic cranial window is permanently secured to the skull following a craniotomy to expose an area of the brain, allowing researchers to image the same location for up to a year . To date, chronic windows have been developed for the brain, skin, lymph node, liver, spleen, and other abdominal organs, and most recently, the lung . Although chronic windows can induce some inflammation when the window is implanted, using this technique to study chronic infections, such as tuberculosis or those seen in cystic fibrosis patients who are plagued by long‐term staphylococcal and Pseudomonas infections, would be of great interest to the medical community.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, the chronic cranial window is permanently secured to the skull following a craniotomy to expose an area of the brain, allowing researchers to image the same location for up to a year . To date, chronic windows have been developed for the brain, skin, lymph node, liver, spleen, and other abdominal organs, and most recently, the lung . Although chronic windows can induce some inflammation when the window is implanted, using this technique to study chronic infections, such as tuberculosis or those seen in cystic fibrosis patients who are plagued by long‐term staphylococcal and Pseudomonas infections, would be of great interest to the medical community.…”
Section: Discussionmentioning
confidence: 99%
“…126 To date, chronic windows have been developed for the brain, skin, lymph node, liver, spleen, and other abdominal organs, and most recently, the lung. 126,127 Although chronic windows can induce some inflammation when the window is implanted, using this technique to study chronic infections, such as tuberculosis or those seen in cystic fibrosis patients who are plagued by long-term staphylococcal and…”
Section: Discussionmentioning
confidence: 99%
“…These have allowed long‐term imaging of the mammary gland and the abdomen . Recently, a longitudinal imaging lung window was added to this list . This lung window made it possible for the first time to visualize tumor cell extravasation in real time (Figure E).…”
Section: Extending and Complementing The Capabilities Of Iv‐mpmmentioning
confidence: 99%
“…While elastin autofluorescence has been useful for ex vivo studies in the lung, so far, no IV‐MPM study of lung elastin has been reported. With the development of the lung imaging window (see section ), we can expect that more longitudinal studies will harness the autofluorescence properties of elastin, abundant in the lung.…”
Section: Translational Potential Of Iv‐mpm For Cancermentioning
confidence: 99%
See 1 more Smart Citation